Beneficial and Pathogenic Arabidopsis Root-Interacting Fungi Differently Affect Auxin Levels and Responsive Genes During Early Infection - Meents, Anja K.; Furch, Alexandra C. U.; Almeida-Trapp, Marília; Özyürek, Sedef; Scholz, Sandra S.; Kirbis, Alexander; Lenser, Teresa; Theißen, Günter; Grabe, Veit; Hansson, Bill; Mithöfer, Axel; Oelmüller, Ralf (Frontiers in Microbiology, 2019)
Auxin (indole-3-acetic acid, IAA) is an important phytohormone involved in root growth and development. Root-interacting beneficial and pathogenic fungi utilize auxin and its target genes to manipulate the performance of their hosts for their own needs. In order to follow and visualize auxin effects in fungi-colonized Arabidopsis roots, we used the dual auxin reporter construct DR5::EGFP-DR5v2::tdTomato and fluorescence microscopy as well as LC-MS-based phytohormone analyses. We demonstrate that the beneficial endophytic fungi Piriformospora indica and Mortierella hyalina produce and accumulate IAA in their mycelia, in contrast to the phytopathogenic biotrophic fungus Verticillium dahliae and the necrotrophic fungus Alternaria brassicicola. Within three hours after exposure of Arabidopsis roots to the pathogens, the signals of the auxin-responsive reporter genes disappeared. When exposed to P. indica, significantly higher auxin levels and stimulated expression of auxin-responsive reporter genes were detected both in lateral root primordia and the root elongation zone within one day. Elevated auxin levels were also present in the M. hyalina/Arabidopsis root interaction, but no downstream effects on auxin-responsive reporter genes were observed. However, the jasmonate level was strongly increased in the colonized roots. We propose that the lack of stimulated root growth upon infection with M. hyalina is not caused by the absence of auxin, but an inhibitory effect mediated by high jasmonate content.